Hydrogen peroxide and disease: towards a unified system of pathogenesis and therapeutics - Jay Pravda (BMC, 2020)
Abstract Although the immune response has a prominent role in the pathophysiology of ulcerative colitis, sepsis, and systemic lupus erythematosus, a primary immune causation has not been established to explain the pathogenesis of these diseases. However, studies have reported significantly elevated levels of colonic epithelial hydrogen peroxide (a known colitic agent) in ulcerative colitis prior to the appearance of colitis. And patients with sepsis are reported to have toxic levels of blood hydrogen peroxide, whose pathologic effects mirror the laboratory and clinical abnormalities observed in sepsis. More recently, evidence supports a causal role for cellular hydrogen peroxide (a potent apoptotic agent) in the enhanced apoptosis believed to be the driving force behind auto-antigenic exposure and chronic immune activation in systemic lupus erythematosus. The different biological properties of hydrogen peroxide exert distinct pathologic effects depending on the site of accumulation within the body resulting in a unique disease patho-phenotype. On a cellular level, the build-up of hydrogen peroxide triggers apoptosis resulting in systemic lupus erythematosus, on a tissue level (colonic epithelium) excess hydrogen peroxide leads to inflammation and ulcerative colitis, and on a systemic level the pathologic effects of toxic concentrations of blood hydrogen peroxide result in bioenergetic failure and microangiopathic dysfunction leading to multiple organ failure and circulatory shock, characteristic of advanced sepsis. The aim of this paper is to provide a unified evidence-based common causal role for hydrogen peroxide in the pathogenesis of ulcerative colitis, sepsis, and systemic lupus erythematosus. Based on this new theory of pathogenesis, a novel evidence-based treatment of sepsis is also discussed.